(untitled) (International Journal of Built Environment and Sustainability, 2025)
Building Information Modeling (BIM) plays a pivotal role not only in construction but also in the continuous evaluation of building energy dynamics. BIM methods provide precise energy performance assessments and consumption evaluations. This study focuses on assessing Energy Use Intensity (EUI) using Autodesk Insight 360 for a case study building and comparing it with traditional manual practices for energy optimization. The UMS Library, which received an Energy Audit Conditional Grant under the RMK11 initiative by KeTTHA, previously relied on manual methods to reduce energy consumption. A detailed 3D model of the UMS Library was created using Autodesk Revit 2023 and analyzed with Autodesk Insight 360 to demonstrate the effectiveness of BIM strategies in enhancing the building envelope, retrofitting, and equipment efficiency. The utilization of BIM tools resulted in a significant reduction in EUI to 60.5 kWh/m²/year compared to the traditional manual methods, which measured 176.27 kWh/m²/year. This improvement significantly enhances energy efficiency per square meter annually. BIM tools prove to be crucial for swift and accurate energy performance assessments, offering superior outcomes compared to manual practices.